Phytochemical studies and biological activities of Garcinia mangostana L., G. nitida Pierre and G. benthamiana (Planch. & Triana) pipoly - See, Irene (2017)
Detailed phytochemical studies on G. mangostana, G. nitida and G. benthamiana have led to the isolation of fourteen compounds, which included four new compounds and ten other compounds. Various chromatographic methods were used in the process of purification of these phytochemical compounds. The structures of these compounds were elucidated by interpreting spectroscopic data obtained from GC-MS, UV, IR, 1D and 2D NMR. The stem bark extracts of G. mangostana furnished ten secondary metabolites, which included three new compounds and seven known compounds. The hexane extract afforded stigmasterol (109) and β-mangostin (100), while the chloroform extract gave cowagarcinone B (101). Isolation work on the ethyl acetate extract yielded two new xanthones, mangaxanthone A (96) and B (97), along with α-mangostin (99), dulcisxanthone F (102), mangostanin (104) and mangostenol (103). The methanol extract gave one new benzophenone, mangaphenone (98). Chromatographic purification of various stem bark extracts of G. nitida resulted in three known compounds from the hexane and chloroform extracts which are stigmasterol (109), osajaxanthone (106) and rubraxanthone (105). The hexane extract of G. benthamianafurnished one known benzophenone, congestiflorone (108) along with one common sterol, stigmasterol (109) and a new benzophenone, benthamianone (107). In silico study was carried out and all the compounds were predicted to effectively induce apoptosis of both cell lines through fatty acid synthase (4PIV). This suggested that all the secondary metabolites would be potential candidates for inhibition of MDA-MB-231 and MCF-7 cells. All the extracts and compounds were subjected to preliminary in vitro screening towards MCF-7, MDA-MB-231 and Vero cell lines. Among all the extracts of these G.species, the ethyl acetate and methanol extracts of G. benthamiana exhibited potent inhibitory effect against MCF-7 and both showed weak cytotoxicities toward Vero cell line. Mangaphenone (98) demonstrated high inhibitory activity against MCF-7 cells but moderate inhibitory activity towards MDA-MB-231 cell line but was weak cytotoxic towards Vero cells. The ethyl acetate and methanol extracts of G. benthamiana showed the highest total phenolic content among all the extracts. The methanol extract of G. nitida had the strongest scavenging ability against DPPH free radical, which was stronger than BHT. Besides, the methanol extract of G. benthamiana demonstrated the most potent reducing ability towards ferric ion while the ethyl acetate extract of G. nitidademonstrated a strong inhibitory effect against β-carotene bleaching. However, all the extracts of the three Garcinia species exhibited weak chelating ability, which was less than 45% chelating power for 500 μg/mL of extract. All the tested compounds exhibited weak antioxidant power. On the other hand, all the G. benthamiana extracts except the methanol extract, had weak activity against Bacillus sublitis and Staphylococcus aureus. All the extracts had no effects against Staphylococcus epidermidis, Escherichia coli and Serratia marcencens.